2020
DOI: 10.1016/j.jaci.2019.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Wiskott-Aldrich syndrome protein senses irradiation-induced DNA damage to coordinate the cell-protective Golgi dispersal response in human T and B lymphocytes

Abstract: Background: Wiskott-Aldrich syndrome (WAS) is an X-linked primary immune deficiency disorder resulting from Wiskott-Aldrich syndrome protein (WASp) deficiency. Lymphocytes from patients with WAS manifest increased DNA damage and lymphopenia from cell death, yet how WASp influences DNA damage-linked cell survival is unknown. A recently described mechanism promoting cell survival after ionizing radiation (IR)-induced DNA damage involves fragmentation and dispersal of the Golgi apparatus, known as the Golgi-dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…(Table 3). Loss-of-function mutations in genes that are involved in genomic stability such as BLM, LIG4, FANCA, FANCC, FANCD2, and presumably WAS may be associated with a high incidence of reversion mutations (3,(51)(52)(53). Gene variation analysis, used to evaluate the mutation frequency of PID genes in which reversion events have or have not been described, has revealed that genetic variation is significantly greater for revertant genes than for nonrevertant or control genes, especially in coding sequences (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 3). Loss-of-function mutations in genes that are involved in genomic stability such as BLM, LIG4, FANCA, FANCC, FANCD2, and presumably WAS may be associated with a high incidence of reversion mutations (3,(51)(52)(53). Gene variation analysis, used to evaluate the mutation frequency of PID genes in which reversion events have or have not been described, has revealed that genetic variation is significantly greater for revertant genes than for nonrevertant or control genes, especially in coding sequences (18).…”
Section: Discussionmentioning
confidence: 99%
“…It also has an important role in correcting existing double strand breaks in human B-cells ( 52 ). Moreover, another study revealed a novel function of WASp in the DNA-damage-induced Golgi dispersal response, and its disruption as a contributor to radiosensitivity in T- and B-cells ( 53 ). WASp accordingly has critical functions in maintaining a stable genome in human T- and B-cells.…”
Section: Pids Associated With Reversion Mosaicismmentioning
confidence: 99%
“…WASP deficiency promotes T-cell cytoskeletal tension decay and phosphorylation of a serine/threonine protein kinase 4 (STK4) that usually increase T-cell migration, therefore promoting immune synapse breaking and secondary B cells dysfunction ( 93 , 94 ). WASP-deficient lymphocytes fails to differentiate into memory cells ( 95 ) and are more prone to develop DNA damages due to the loss of the Golgi-dispersal response, a recently described mechanism of cell survival after ionized radiation exsposure ( 96 ). The STK4 deficiency causes a PID characterized by B and T cell lymphopenia, neutropenia, and cardiac malformations (no.…”
Section: Introductionmentioning
confidence: 99%
“…WAS patients are prone to developing malignancies of poor prognosis and most frequently lymphoreticular tumors including non-Hodgkin lymphoma (76% of the total tumors associated with WAS), Hodgkin lymphoma, and Burkitt lymphoma ( 46 – 50 ). Both reduced tumor immunosurveillance by cytotoxic cells ( 15 , 30 34 , 37 39 ) and intrinsic cell transformation ( 15 , 51 , 52 ) contribute to malignancies in WAS. In the family with WASp L270P XLN ( 1 ), 2 out of 6 affected males have developed myelodysplastic syndrome and leukemia, and 1 unrelated patient with the WASp I294T mutation developed myelodysplastic syndrome ( 2 ).…”
Section: Discussionmentioning
confidence: 99%